Integrating Managerial Supervision and Clinical Supervision to Improve Teacher Performance in Islamic Educational Institutions - Lalu Wirasantana; Edi Muhamad Jayadi; Muhammad Muhammad (PT. Riset Press International, 2026)
This study aims to analyze the integration of managerial supervision and clinical supervision in improving teacher performance within Islamic educational institutions through a Systematic Literature Review (SLR) approach. The review draws on scholarly articles indexed in Scopus, DOAJ, and Google Scholar, with a publication range limited to the last ten years to ensure the relevance and currency of findings. The selection process followed rigorous inclusion and exclusion criteria, focusing on empirical and conceptual studies that address supervision practices in educational contexts, particularly within Islamic institutions. The findings indicate that managerial supervision plays a critical role in establishing a strong organizational foundation through effective planning, coordination, leadership, and resource management. This form of supervision contributes to the creation of a conducive academic climate that supports teacher professionalism and institutional effectiveness. Meanwhile, clinical supervision emphasizes direct, reflective, and collaborative interactions between supervisors and teachers, fostering continuous pedagogical improvement and instructional quality. The integration of these two supervisory approaches demonstrates a complementary relationship, where managerial supervision ensures systemic support and institutional alignment, while clinical supervision enhances individual teacher competence and classroom practices. This synergy leads to more sustainable improvements in teacher performance, professional development, and overall educational quality. The study contributes to the advancement of educational supervision literature by providing a comprehensive conceptual framework that integrates managerial and clinical supervision within Islamic educational settings. Furthermore, it enriches the body of knowledge by highlighting the synergistic mechanisms through which both supervisory approaches can be implemented to strengthen teacher professionalism and institutional effectiveness, offering a foundation for future empirical research and policy development in educational management and supervision. The study concludes that a balanced and integrated supervision model is essential for strengthening teacher performance and achieving educational excellence in Islamic educational institutions.